Phytochemical and pharmacological study of aesculus indica linn. Plant: An updated review - Neha Kaushik; Manjusha Choudhary; Ashwani Jangra (Wolters Kluwer Medknow Publications, 2021)
Objective: Aesculus indica Linn. commonly known as Indian horse chestnut belongs to family hippocastanaceae. It is extensively used in folk medicine. The whole plant is proved to possess beneficial therapeutic activities like anti-tumour, anti-diabetic and anti-oxidant etc. However no approved marketed formulation of any of its active ingredients is available in any country of the world till date. There is also a subtle mention of its toxicity in some studies. Its uses can be exploited commercially in a better way if its active pharmaceutical ingredients are able to be separated from its toxic ingredients. Succinctly, the plant can be used commercially in future only when its toxicity is managed somehow. The review briefly summarizes its beneficial effects and the problem associated with it as a counterpart with a brief mention of on-going medicinal research on it. Data Source: The data is collected from different databases i.e. Science Direct, PubMed, Google and Google Scholar. Review Methods: Bibliographic investigation was carried out by analysing various research and review papers. Results and Conclusion: Aesculus indica can be used to develop variety of products with high nutritional and medicinal values. The compound Aescin (a triterpenoids saponin) has been isolated from this plant and i.e. used to prevent several ailments such as rheumatism, skin diseases, relieve headache and wound healing. It also contains some phytoconstituents which have high potency to be used in cosmetics.